Analisis Pada Force Majeure Dalam Akad Murabahah Dan Dampak Implementasi Pada Lembaga Keuangan Syariah - An Nisaa' Anggun Febriana; Dhika Afnan Rolina; Indah Ayu Sukmawati; Agus Eko Sujianto (Journal of Creative Student Research, 2023)
This study aims to determine and analyze the position of force majeure in murabahah contracts and how the implementation of force majeure in murabahah contracts in Sharia Financial Institutions. This study uses normative legal research supported by empirical data. Data collection techniques used by the author is the study of literature documents that are examined from books, literature, journals, and legislation. The conclusion of this research is first, the position of force majeure in the murabahah contract is a necessity to anticipate unwanted and dangerous circumstances, which are beyond the authority of the parties in the murabahah contract. In addition, Islamic law also regulates positions related to force majeure that is known as dharurah, which means damaging or giving harm. Second, the implementation of force majeure in the murabahah contract at the Sharia Financial Institution has already been applied in the contract or agreement by the parties. Force majeure clause becomes a reason not to charge the parties for losses arising from force majeure events that occur. Something that is allowed due to dharurah conditions, must be completed according to the required size restrictions.